Low level bacterial endotoxin activates two distinct signaling pathways in human peripheral blood mononuclear cells - Weintraub Neal L; Dickson Eric W; Romig-Martin Sara A; Shaheen Wassim; Stoll Lynn L; Blomkalns Andra L; Denning Gerene M (BMC, 2011)
Abstract Background Bacterial endotoxin, long recognized as a potent pro-inflammatory mediator in acute infectious processes, has more recently been identified as a risk factor for atherosclerosis and other cardiovascular diseases. When endotoxin enters the bloodstream, one of the first cells activated is the circulating monocyte, which exhibits a wide range of pro-inflammatory responses. Methods We studied the effect of low doses of E. coli LPS on IL-8 release and superoxide formation by freshly isolated human peripheral blood mononuclear cells (PBMC). Results IL-8 release was consistently detectable at 10 pg/ml of endotoxin, reaching a maximum at 1 ng/ml, and was exclusively produced by monocytes; the lymphocytes neither produced IL-8, nor affected monocyte IL-8 release. Superoxide production was detectable at 30 pg/ml of endotoxin, reaching a maximum at 3 ng/ml. Peak respiratory burst activity was seen at 15-20 min, and superoxide levels returned to baseline by 1 h. IL-8 release was dependent on both membrane-associated CD14 (mCD14) and Toll-like receptor 4 (TLR4. Superoxide production was dependent on the presence of LBP, but was not significantly affected by a blocking antibody to TLR4. Moreover, treatment with lovastatin inhibited LPS-dependent IL-8 release and superoxide production. Conclusions These findings suggest that IL-8 release and the respiratory burst are regulated by distinct endotoxin-dependent signaling pathways in PBMC in low level of endotoxin exposure. Selectively modulating these pathways could lead to new approaches to treat chronic inflammatory diseases, such as atherosclerosis, while preserving the capacity of monocytes to respond to acute bacterial infections.